Memory Trick Game Towards Students’ Enthusiasm In Learning Grammar - Setianingsih, Tri; Nafisah, Bq Zuhrotun (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This was a qualitative research and aimed to investigate whether how memory trick game could improve students in learning grammar at SMPN 18 Mataram in the academic year of 2019/2020. The subject of this research was the second grade students of SMPN 18 Mataram that only one class consist of 15 students. This research was limited by the grammatical role only. The research instruments consisted of questionners, field note, and documentation. The data analyzed in transcript for the observation and taking note for shows that the students at SMPN 18 Mataram still low enthusiasm and comprehend the Memory Trick Game. The researcher took the research and has the provident which the questioner was looking for the students’ surface knowledge about the what is grammar and how enthusiasm student in learning grammar. The result of cycling process also shows that in the first cycle consist of three meetings, and the students were still need to be more concentrate in order to make them more understand in expanding their ideas into a good grammar. Then the cycle two was also consist of three meetings, the students’ score in this cycle was better than the cycle one. The memory trick game as the solution from the researchers also proved that there was an improvement from the first cycle to the second cycle.